Total Strategy of Maritime Defense Diplomacy Facing the Threat of Natural Disasters in the South Pacific - Mahroza, Jonni; Prakoso, Lukman Yudho; Andriyanto, Agus; Yulivan, Ivan; Susmoro, Harjo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The presence of major countries in the Indo-Pacific region has brought various impacts to regional countries including Indonesia. In addition to bringing benefits with increasing economic levels, there are also threats to security stability in the region. The purpose of this article's research is to analyze the Impact of the Total Strategy of Maritime Defense Diplomacy in Facing the Dynamics of the Strategic Environment in the South Pacific. The method used is descriptive qualitative. The results of the study are that Indonesia's total strategy of maritime defense diplomacy in the South Pacific has succeeded in managing the dynamics of the strategic environment by integrating military, humanitarian, and diplomatic aspects. Through joint exercises, humanitarian assistance, and maritime diplomacy, Indonesia has strengthened its disaster mitigation capacity, increased regional stability, and strengthened diplomatic relations.